Development and Validation of a Seismic Index for Assessing the Vulnerability of Low-Rise RC Buildings - Sharafi, Sayed Q.; Maulana, Taufiq I.; Saito, Taiki (Civil Engineering Journal, 2025)
This research develops a comprehensive framework for evaluating the seismic vulnerability of Afghanistan's low-rise reinforced concrete (RC) structures, aiming to enhance urban resilience and mitigate seismic risks. The primary objective is to improve structural safety and reduce economic losses and casualties during devastating earthquakes. Utilizing a database of low-rise RC buildings constructed between 2001 and 2022 by the Ministry of Urban Development and Housing (MUDH) and the Ministry of Education (MOE), the study analyzes structures with varying materials, architectural styles, construction years, and number of stories. The methodology integrates a modified Japanese Is Index, refined using statistical techniques to incorporate local seismic data and building characteristics across diverse seismic zones. Advanced analyses, including the Capacity Spectrum Method (CSM) and dynamic analysis using STERA 3D software, support the development of the Afghanistan Seismic Index (ASI). Findings confirm ASI’s reliability by comparing it to existing seismic assessment methods, demonstrating its suitability for region-specific evaluations. The research proposes a novel, tailored seismic index (ASI) for assessing seismic vulnerability and addressing gaps in Afghanistan’s building code (ABC) and standards. This framework enhances structural performance and informs future policy, providing a foundation for safer urban environments and sustainable infrastructure development in earthquake-prone regions. Doi: 10.28991/CEJ-2025-011-03-016 Full Text: PDF